2019
DOI: 10.1016/j.surg.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Financial implications of telemedicine visits in an academic endocrine surgery program

Abstract: Background: Telemedicine is an emerging medium for the delivery of ambulatory care, but the reimbursement profile of telemedicine visits in the surgical setting has not been well studied. Methods: A retrospective assessment of telemedicine encounters for thyroid and parathyroid conditions occurring from April 2015 to April 2017 was performed. Financial reimbursement from commercial payers for new and established patient visits were compared between telemedicine visits and in-person visits. Patient "savings" in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
(9 reference statements)
0
23
0
1
Order By: Relevance
“…The methods were used and reported in previous literature involving telemedicine. 19 In our patient cohort, 14 zip codes were not entered into the EMR; hence, our time savings analysis was based on 405 subjects. We estimated the travel time with traffic by assuming morning telemedicine encounters occurring at 10 am and afternoon encounters beginning at 1 pm .…”
Section: Methodsmentioning
confidence: 99%
“…The methods were used and reported in previous literature involving telemedicine. 19 In our patient cohort, 14 zip codes were not entered into the EMR; hence, our time savings analysis was based on 405 subjects. We estimated the travel time with traffic by assuming morning telemedicine encounters occurring at 10 am and afternoon encounters beginning at 1 pm .…”
Section: Methodsmentioning
confidence: 99%
“…First, video visits eliminate or reduce patients' time spent waiting to see their doctors (2)(3)(4). Video visits also eliminate travel time for patients (5,6). Finally, video visits may reduce caretaker burden.…”
Section: Original Articlementioning
confidence: 99%
“…[93,94] However, before implementing the telemedicine program, issues regarding patient privacy, financial reimbursement and technological platforms' reliability should be considered. [95] Previous studies have demonstrated the applicability of telemedicine in a wide range of applications, from diabetic retinopathy screening to postoperative visits for pediatric urology. Surgical procedures, such as inguinal or umbilical hernia repair, have been found to be particularly suitable for telemedicine encounters since these operations are associated with relatively lower complications that require faceto-face evaluation or intervention.…”
Section: Telemedicine In Endocrine Surgerymentioning
confidence: 99%